A special polishing slurry and polishing method for β-Ga2O3 (100) with a 6° off-center crystal plane.

CN122706255APending Publication Date: 2026-09-08SUZHOU LIAOYUAN SEMICON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610945976.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-09-08

AI Technical Summary

Technical Problem

然而,针对β-Ga2O3(100)偏6°晶面的专用抛光液及抛光工艺,现有技术的相关报道较少,因此,急需开发出一种适用于β-Ga2O3(100)偏6°晶面的高效、低损伤抛光液及抛光方法

Benefits of technology

(1)本发明采用“强酸性粗抛+酸性精抛”两段式工艺,粗抛阶段利用pH为1~2的强酸性环境,充分发挥高浓度H+对Ga-O键的强进攻能力,材料去除速率达2.5~4μm/h,远优于碱性抛光液;粗抛仅需3~4小时、精抛仅需1.5小时,无需复杂设备改造或特殊耗材,加工效率高、成本可控,适用于β-Ga2O3(100)偏6°衬底的批量制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122706255A_ABST
    Figure CN122706255A_ABST
Patent Text Reader

Abstract

This invention relates to a special polishing slurry and polishing method for β-Ga2O3 (100) with a 6° offset crystal plane, belonging to the field of semiconductor material processing technology. The polishing slurry includes a strongly acidic coarse polishing slurry and an acidic fine polishing slurry. The coarse polishing slurry is composed of acidic silica sol with an average particle size of 110-130 nm, hydrogen peroxide, citric acid, phosphoric acid, and deionized water, with a pH of 1-2. The fine polishing slurry is composed of acidic silica sol with an average particle size of 15-30 nm, hydrogen peroxide, and deionized water. The polishing process employs a two-stage method: coarse polishing uses a white non-woven fabric pad, with a rotation speed of 30-40 rpm, a pressure of 260 gf / cm², and a time of 3-4 hours; fine polishing uses a black frosted leather pad, with a rotation speed of 20-30 rpm, a pressure of 200 gf / cm², and a time of 1.5 hours. This invention can achieve a high removal rate of 2.5~4μm / h, a polished surface without scratches or pits, a roughness Ra≤0.12nm, and an XRD half-width <50 arcseconds, making it suitable for mass production of high-quality β-Ga2O3(100) 6° biased substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor material processing technology, specifically relating to a special polishing slurry and polishing method for β-Ga2O3 (100) with a 6° offset crystal plane. Background Technology

[0002] β-Ga₂O₃ (β-phase gallium oxide) possesses a bandgap (4.9 eV) far exceeding that of silicon carbide and gallium nitride, as well as a high breakdown electric field strength (8 MV / cm), and is expected to play a significant role in high-power power electronic devices and deep ultraviolet detectors. β-Ga₂O₃ is a monoclinic crystal with significant differences in lattice constants across its three faces: a = 1.232 nm, b = 0.304 nm, and c = 0.580 nm. This results in highly anisotropic properties, with different crystal faces exhibiting varying hardness and chemical activity, such as (100), (100) 6° offset ((100) 6° offset in the [00-1] direction), (001), (-201), and (010). Furthermore, the presence of two cleavage planes, (100) and (001), in β-Ga₂O₃ makes the fabrication of β-Ga₂O₃ substrates extremely difficult.

[0003] Compared to other crystal planes, the β-Ga2O3(100) 6° off-center crystal plane has lower hardness and is less prone to cleavage, making it easier to fabricate large-size substrates and facilitating mass production. Furthermore, this crystal plane can achieve step-flow growth in epitaxial processes such as MOCVD and HVPE, enabling the production of high-quality homoepitaxial layers with a thickness greater than 20 μm, possessing significant industrial application value. However, there are few reports on dedicated polishing slurries and polishing processes for the β-Ga2O3(100) 6° off-center crystal plane. Therefore, there is an urgent need to develop an efficient, low-damage polishing slurry and polishing method suitable for the β-Ga2O3(100) 6° off-center crystal plane. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a dedicated polishing slurry and polishing method for β-Ga2O3 (100) 6° off-center crystal planes. By combining coarse polishing with a strong acid system and fine polishing with an acid system, a super-smooth β-Ga2O3 (100) 6° off-center crystal plane single crystal substrate with high substrate removal rate, low surface roughness, no pits, and no micro-scratches can be prepared.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: On the one hand, a special polishing solution for β-Ga2O3 (100) with a 6° offset crystal plane is provided, including a strong acid coarse polishing solution and an acidic fine polishing solution; The strongly acidic coarse polishing solution comprises, by volume,: 28-32 parts by volume of the first acidic silica sol; 4.5 to 5.5 parts by volume of hydrogen peroxide with a mass fraction of 30%; 1.8 to 2.2 parts by volume of a 50.3% citric acid aqueous solution; 0.08~0.12 parts by volume of an 85% phosphoric acid aqueous solution; 55-65 parts by volume of deionized water; The first acidic silica sol has an average particle size of 110 nm to 130 nm, a SiO2 mass fraction of 39% to 41%, and a pH value of 2.0 to 4.0. The pH value of the strongly acidic coarse polishing solution is 1~2; The acidic polishing solution comprises, by volume,: 15 parts by volume of the second acidic silica sol; 3 volumes of hydrogen peroxide with a mass fraction of 30%; 32 parts by volume of deionized water; The second acidic silica sol has an average particle size of 15nm~30nm, a SiO2 mass fraction of 24%~26%, and a pH value of 2.0~4.0.

[0006] On the other hand, a polishing method for a β-Ga2O3 (100) 6° offset crystal plane is provided, which uses the above-mentioned special polishing liquid to perform segmented polishing on the pretreated β-Ga2O3 (100) 6° offset single crystal, specifically including a rough polishing process and a fine polishing process; The rough polishing process specifically includes: The pretreated β-Ga2O3 (100) 6° offset single crystal was fixed on a ceramic carrier and placed in a polishing machine. A white non-woven polishing pad was used, and the strong acid coarse polishing liquid was supplied for polishing. The polishing disc rotation speed is 30 rpm to 40 rpm, the polishing pressure is 260 gf / cm², the flow rate of the strong acid coarse polishing solution is 100 mL / min, and the coarse polishing time is 3 h to 4 h. The white non-woven polishing pad has a thickness of 1.3 mm, a hardness of 85, and a compression rate of 3%. The fine polishing process specifically includes: A black frosted leather polishing pad is used, and the fine polishing liquid is supplied for polishing; The polishing disc rotation speed is 20 rpm to 30 rpm, the polishing pressure is 200 gf / cm², the fine polishing solution flow rate is 80 mL / min, and the fine polishing time is 1.5 h. The black frosted leather polishing pad has a thickness of 1.45mm, a warp tensile strength of 642N / cm³, a weft tensile strength of 511N / cm³, a warp elongation at break of 53%, a weft elongation at break of 86%, a warp tear strength of 57N, and a weft tear strength of 56N.

[0007] The beneficial effects of this invention are as follows: (1) The present invention adopts a two-stage process of “strong acid coarse polishing + acid fine polishing”. The coarse polishing stage utilizes a strong acidic environment with a pH of 1~2 to give full play to the high concentration of H + It has a strong attack capability on Ga-O bonds, and the material removal rate reaches 2.5~4μm / h, which is far superior to alkaline polishing liquid. Rough polishing only takes 3~4 hours and fine polishing only takes 1.5 hours. No complex equipment modification or special consumables are required. It has high processing efficiency and controllable cost, and is suitable for the batch preparation of β-Ga2O3(100) offset 6° substrates.

[0008] (2) This invention achieves precise matching of chemical etching and mechanical grinding by matching silica sol with different particle sizes and polishing pads. Coarse polishing uses large-particle-size, high-solid-content silica sol with a white non-woven polishing pad to efficiently remove macroscopic damage left by pretreatment; fine polishing uses small-particle-size silica sol with a high-toughness black frosted leather polishing pad to gently eliminate microscopic scratches and avoid secondary damage. After polishing, the wafer surface is free of scratches, pits, and hazy defects, with a surface roughness Ra≤0.12nm, achieving atomic-level smoothness; the half-width at half-maximum (WHM) of the sample XRD rocking curve is less than 50 arcseconds, which can effectively remove the subsurface damage layer and provide a high-quality substrate for high-quality epitaxial growth.

[0009] (3) Through comparative experiments, the present invention can accurately match the structural features of (100) offset 6°, and achieve optimized synergy between chemical etching and mechanical removal. Compared with the problems of dense scratches, low removal rate and easy corrosion pits after polishing of crystal surfaces such as (010), (011), (001), (100), and (-201), the present invention can quickly obtain a defect-free ultra-smooth surface β-Ga2O3 (100) offset 6° substrate, effectively solving the polishing processing technical problem of this special crystal surface.

[0010] This invention introduces phosphoric acid into the coarse polishing solution, which can dynamically stabilize the pH value of the polishing environment, effectively avoiding local over-corrosion or passivation problems caused by microscopic morphology differences on the (100) 6° wafer surface, and completely eliminating defects such as hazy spots and uneven polishing. At the same time, hydrogen peroxide in the formula can precisely control the oxidation reaction rate, and citric acid ensures uniform corrosion and removal of the entire wafer, greatly improving the stability and processing consistency of the polishing solution system. Attached Figure Description

[0011] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0012] Figure 1 This is a wafer surface topography diagram of Embodiment 1 of the present invention; Figure 2 The results of AFM testing on the wafer surface are shown in Embodiment 1 of the present invention. Detailed Implementation

[0013] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0014] To ensure the accuracy of the experiment, in the following examples and comparative examples, the β-Ga2O3 (100) offset by 6° ((100) offset by 6° in the [00-1] direction) substrates were all single wafers of the same specifications obtained by the same crystal cutting and pre-processing method, with a wafer size of 10mm × 10mm. The pre-processing method included wafer thinning, grinding, etc. During the polishing experiment, three wafers to be processed were evenly pasted on a circular ceramic carrier with a diameter of 138mm.

[0015] Example 1

[0016] A method for preparing a special polishing slurry for β-Ga2O3 (100) with a 6° off-center crystal plane includes the following steps: S1. Preparation of strongly acidic coarse polishing solution: Take 30 parts by volume of the first acidic silica sol with an average particle size of 110nm~130nm, a SiO2 mass fraction of 39%~41%, and a pH value of 2.0~4.0; Take 5 volumes of hydrogen peroxide with a mass fraction of 30%; Take 2 volumes of a 50.3% citric acid aqueous solution; Take 0.1 volume parts of an 85% phosphoric acid aqueous solution; Take 60 volume portions of deionized water; Mix the above components thoroughly to obtain a strongly acidic crude polishing solution with a pH of 1.8. S2. Preparation of acidic polishing solution: Take 15 volumes of a second acidic silica sol with an average particle size of 15nm~30nm, a SiO2 mass fraction of 24%~26%, and a pH value of 2.0~4.0; Take 3 volumes of hydrogen peroxide with a mass fraction of 30%; Take 32 volume portions of deionized water; Mix the above components thoroughly to obtain the acidic polishing solution.

[0017] The strongly acidic coarse polishing solution and acidic fine polishing solution prepared in this embodiment were used to polish the wafer to be processed. The wafer to be processed was a 10mm×10mm β-Ga2O3 (100) 6° offset single wafer after thinning and grinding pretreatment. The specific polishing steps included: S1. Rough polishing process The single crystal wafer is bonded to a ceramic carrier using solid wax and then placed in a polishing machine; The polishing pad is a white non-woven polishing pad with a thickness of 1.3mm, a hardness of 85, and a compression rate of 3%. White non-woven polishing pads have a special microporous structure, which provides excellent retention of polishing fluid while maintaining moderate rigidity, thus improving processing stability and dimensional accuracy. White non-woven polishing pads are characterized by high efficiency, scratch-free operation, long service life, good elasticity, and gentle force application.

[0018] The polishing disc rotation speed was set to 35 rpm, the polishing pressure to 260 gf / cm², and the strong acid coarse polishing solution prepared in this embodiment was continuously supplied at a flow rate of 100 mL / min for a coarse polishing time of 3 h. S2, Fine Polishing Process After rough polishing, the single crystal is cleaned and placed in a polishing machine; The polishing pad is made of black matte leather, with a thickness of 1.45 mm and a warp tensile strength of 642 N / cm². 3 The latitudinal tensile strength is 511 N / cm. 3 The elongation at break in the warp direction is 53%, the elongation at break in the weft direction is 86%, the tear strength in the warp direction is 57N, and the tear strength in the weft direction is 56N. The polishing disc rotation speed was set to 25 rpm, the polishing pressure to 200 gf / cm², and the acidic fine polishing solution prepared in this embodiment was continuously supplied at a flow rate of 80 mL / min for a fine polishing time of 1.5 h. After polishing, the wafers are cleaned and dried.

[0019] The surface quality of the wafer was characterized using differential interference microscopy and atomic force microscopy (AFM), and the material removal rate was calculated using the gravimetric method.

[0020] Tests showed that during the rough polishing stage, the material removal rate was 3μm / h, the wafer surface had only a few shallow scratches, and the surface roughness was less than 5nm.

[0021] During the fine polishing stage, the material removal rate was 0.2 μm / h. See [link / reference]. Figure 1 After fine polishing, the wafer surface is free of micro-scratches, pits, and other defects. (See also...) Figure 2 AFM testing showed that the crystal surface roughness Ra was less than 0.11 nm, achieving an atomically smooth surface. The full width at half maximum (FWHM) of the high-resolution X-ray rocking curves was less than 50 arcseconds, indicating that the special polishing solution and polishing method of this invention achieved a good balance between chemical corrosion and mechanical removal, effectively removing the sub-damaged layer left by the pretreatment.

[0022] The efficiency of Chemical Mechanical Polishing (CMP) is determined by both chemical etching and mechanical grinding, with pH directly affecting the rate of chemical etching. This embodiment uses a strongly acidic coarse polishing solution (1≤pH≤2), which has a better chemical etching effect and can generate a softening layer on the surface of a (100)-6 degree gallium oxide wafer that is more conducive to mechanical removal.

[0023] For the (100) 6° off-center crystal plane, the large number of atomic steps introduced by the off-center cutting are preferentially and rapidly corroded in a strong acid environment with pH=1~2, which greatly improves the initial rate and uniformity of material removal.

[0024] Example 2

[0025] This embodiment is basically the same as Embodiment 1, except that the component ratio of the strong acid coarse polishing solution is adjusted.

[0026] S1. Preparation of strongly acidic coarse polishing solution: Take 28 volumes of a first acidic silica sol with an average particle size of 110nm~130nm, a SiO2 mass fraction of 39%~41%, and a pH value of 2.0~4.0; Take 4.5 volume parts of hydrogen peroxide with a mass fraction of 30%; Take 1.8 volume parts of a 50.3% citric acid aqueous solution; Take 0.08 parts by volume of an 85% phosphoric acid aqueous solution; Take 65 volume portions of deionized water; Mix thoroughly, the pH of the system is 1.9; S2, Preparation of Acidic Polishing Solution It is exactly the same as Example 1.

[0027] In the polishing process, the rough polishing time is 4 hours and the fine polishing time is 1.5 hours. The other process parameters, such as rotation speed, pressure, and polishing pad, are exactly the same as in Example 1.

[0028] Tests showed that during the rough polishing stage, the material removal rate was 2.6 μm / h, the wafer surface had only a few shallow scratches, and the surface roughness was less than 5 nm.

[0029] After polishing, the wafer surface is free of micro-scratches and pits, and the surface roughness Ra is less than 0.12nm.

[0030] Comparative Example 1

[0031] In this embodiment, 1 volume of silica sol with an average particle size of 110nm~130nm, a silica mass fraction of 49%~51%, and a pH value of 9.0~10.5 is taken, and 2 volume of deionized water is taken and mixed evenly to prepare an alkaline coarse polishing solution.

[0032] Using the same rough polishing process parameters as in Example 1, namely the same rotation speed, pressure, polishing pad, etc., and a rough polishing time of 8 hours, the material removal rate was tested to be only 0.75 μm / h, which is significantly lower than the removal rate of the acidic rough polishing solution in the present application.

[0033] Comparative Example 2

[0034] This comparative example is basically the same as Example 1, except that the phosphoric acid component is removed from the acidic crude polishing solution formulation, while keeping the other components and proportions unchanged.

[0035] Based on the crude polishing solution formulation of Example 1, phosphoric acid was completely removed, while the remaining components and proportions remained unchanged. The above components were mixed evenly to obtain an acidic crude polishing solution.

[0036] The wafer was polished using the same rough polishing process as in Example 1. After rough polishing, uneven corrosion was visible on the wafer surface, with hazy spots appearing in some areas.

[0037] Phosphoric acid is a moderately strong tribasic acid. In strongly acidic systems with a pH of 1-2, H3PO4 and H2PO4... - Forming a buffer pair, where local areas consume H due to chemical reactions + At that time, H2PO4 - Ionizable to supplement H + To maintain pH stability; when H + When localized enrichment occurs, it can bind with the material. This buffering ability effectively prevents localized over-acidity or over-alkaliness, ensuring the uniformity of chemical etching across the entire wafer surface.

[0038] This comparative example lacks phosphate, and the coarse polishing solution loses its pH buffering capacity. Due to the high surface roughness of the wafers after polishing, surface protrusions or pits negatively impact pH.+ The consumption rates differ significantly. In H + In areas of rapid consumption, the solution pH rises rapidly, leading to a decrease in the corrosion rate and resulting in passivation-type uneven corrosion; while in areas of high pH... + In areas of high pH concentration, the pH drops sharply, and the highly acidic environment triggers localized over-corrosion, forming microscopic etching pits. The cumulative effect of pH instability ultimately manifests as macroscopically visible uneven corrosion and hazy spot defects on the wafer surface.

[0039] Comparative Example 3

[0040] The difference between this comparative example and Example 1 is that the hydrogen peroxide component is removed from the acidic coarse polishing solution formulation, while the other components and proportions remain unchanged.

[0041] Based on the rough polishing solution formulation of Example 1, hydrogen peroxide was completely removed, while the remaining components and proportions remained unchanged. The components were mixed evenly to obtain the rough polishing solution. The wafers were then rough polished using the exact same rough polishing process as in Example 1.

[0042] After rough polishing, a large number of scratches appeared on the substrate surface, and the removal efficiency dropped significantly to only 0.9 μm / h.

[0043] The polishing process involves both chemical and mechanical actions. After removing hydrogen peroxide, the chemical action is significantly weakened, while the mechanical action is much stronger. The force between the polishing pad and the single crystal wafer causes a large number of scratches on the substrate surface, which does not meet the standard for fine polishing.

[0044] Comparative Example 4

[0045] Using the same coarse polishing solution, fine polishing solution, and two-stage polishing process as in Example 1, β-Ga2O3 substrates with six crystal planes (100) offset 6°, (010), (011), (001), (100), and (-201) were polished. The polishing process parameters, such as rotation speed, polishing pressure, time, and polishing pad, were exactly the same.

[0046] To ensure the accuracy of the experiments, in this comparative example, the substrates used for experiments on different crystal planes were all single-wafer wafers obtained by cutting the same crystal and using the same pre-processing method. The wafer size was 10mm × 10mm. The pre-processing method included crystal cutting, thinning, and grinding. During the experiment, three substrates with the same crystal plane were uniformly pasted onto a circular ceramic disk with a diameter of 138mm and subjected to rough polishing and fine polishing. The experimental results are shown in Table 1.

[0047] Table 1 (100) deviates by 6° Time: 3h; Rate: 2~4μm / h; Surface: Several scratches Time: 1.5 hours; Surface: No scratches No scratches (010) Time: 3 hours; Rate: 2-4 μm / h; Surface: Many scratches Time: 1.5h; Surface: Limited scratch removal Numerous densely distributed scratches (011) Time: 3 hours; Rate: 2-4 μm / h; Surface: Many scratches Time: 1.5h; Surface: Limited scratch removal Numerous densely distributed scratches (001) Time: 3h; Rate: 2~4μm / h; Surface: Number of scratches is more than (100) deviates by 6°, and the number is countable. Time: 1.5h + n × 0.5h Surface: Scratches appear on the edges, requiring multiple polishing cycles. No scratches (100) Time: 3h; Rate: 2~4μm / h; Surface: Number of scratches more than 100, deviating from 6°, countable. Time: 1.5h + n × 0.5h Surface: Scratches appear on the edges, requiring multiple polishing cycles. No scratches (-201) Rate: Extremely slow removal; removing 1μm requires 3-4 hours. Surface: Corrosion pits. - -

[0048] It is evident that, under identical polishing conditions, the processing of different crystal planes exhibits significant differences. The polishing slurry provided by this invention has the best polishing effect on the (100) 6° offset crystal plane, with very few scratches after rough polishing, and a scratch-free and defect-free substrate can be obtained after 1.5 hours of fine polishing, resulting in a good wafer surface after etching.

[0049] In contrast, although the rough polishing removal rate of the (010) and (011) crystal planes is similar to that of (100) with a deviation of 6°, a large number of scratches remain on the surface after rough polishing, and the scratch removal is extremely limited after 1.5 hours of fine polishing. After corrosion, the surface shows a dense scratch morphology, indicating that the rough polishing liquid of the present invention has low chemical reaction activity on these two crystal planes, and mechanical action dominates in material removal. As a result, the depth of the subsurface damage layer introduced is large, and the mechanical scratches are more dense after rough polishing.

[0050] After rough polishing, the number of scratches on the (001) and (100) crystal surfaces is more than that on (100) by 6°. After 1.5 hours of fine polishing, there are several scratches on the edge of the wafer. It is necessary to add more fine polishing time. The removal of scratches in the edge area is observed every half hour. This process is repeated multiple times (n×0.5h) until a scratch-free surface is finally obtained. The polishing efficiency is poor.

[0051] (-201) The rough polishing removal rate of the crystal surface is extremely low, and corrosion pits appear on the surface. The wafer after rough polishing does not meet the requirements for further fine polishing.

[0052] The above results clearly demonstrate that the anisotropy of β-Ga2O3 has a decisive influence on its chemical mechanical polishing. The differences in chemical activity of different crystal facets lead to different coupling mechanisms between mechanical wear and chemical corrosion in acidic coarse polishing solutions. For the (010) and (011) crystal facets, due to the relatively dense surface atoms and more stable chemical passivation layer, mechanical removal is difficult to effectively strip the reaction products; while the (-201) crystal facet may result in an extremely low corrosion rate and the formation of corrosion pits due to the excessively slow corrosion reaction or anisotropic dissolution. In contrast, the (100) 6° off-center crystal facet achieves an optimal balance between mechanical and chemical action in this polishing solution system, thus obtaining the best surface quality.

[0053] It can be seen that the polishing liquid and polishing process of the present invention have obvious crystal plane applicability. For crystal planes other than (100) with a deviation of 6°, it is necessary to develop a suitable polishing system according to their respective anisotropic characteristics in order to obtain the ideal processing effect.

[0054] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A special polishing slurry for β-Ga2O3 (100) crystals with a 6° offset, characterized in that, Including strongly acidic coarse polishing solution and acidic fine polishing solution; The strongly acidic coarse polishing solution comprises, by volume,: 28-32 parts by volume of the first acidic silica sol; 4.5 to 5.5 parts by volume of hydrogen peroxide with a mass fraction of 30%; 1.8 to 2.2 parts by volume of a 50.3% citric acid aqueous solution; 0.08~0.12 parts by volume of an 85% phosphoric acid aqueous solution; 55-65 parts by volume of deionized water; The first acidic silica sol has an average particle size of 110 nm to 130 nm, a SiO2 mass fraction of 39% to 41%, and a pH value of 2.0 to 4.

0. The pH value of the strongly acidic coarse polishing solution is 1~2; The acidic polishing solution comprises, by volume,: 15 parts by volume of the second acidic silica sol; 3 volumes of hydrogen peroxide with a mass fraction of 30%; 32 parts by volume of deionized water; The second acidic silica sol has an average particle size of 15nm~30nm, a SiO2 mass fraction of 24%~26%, and a pH value of 2.0~4.

0.

2. A polishing method for β-Ga2O3(100) crystal planes with a 6° offset, characterized in that, Using the special polishing slurry as described in claim 1, the pretreated β-Ga2O3 (100) 6° offset single crystal wafer is polished in segments, including a rough polishing process and a fine polishing process.

3. The polishing method for β-Ga2O3 (100) with a 6° off-center crystal plane according to claim 2, characterized in that, The pretreatment includes thinning and grinding.

4. The polishing method for β-Ga2O3 (100) with a 6° off-center crystal plane according to claim 3, characterized in that, The rough polishing process specifically includes: The pretreated β-Ga2O3 (100) 6° offset single crystal was fixed on a ceramic carrier and placed in a polishing machine. A white non-woven polishing pad was used, and the strong acid coarse polishing liquid was supplied for polishing. The polishing disc rotation speed is 30 rpm to 40 rpm, the polishing pressure is 260 gf / cm², the flow rate of the strong acid coarse polishing solution is 100 mL / min, and the coarse polishing time is 3 h to 4 h. The white non-woven polishing pad has a thickness of 1.3 mm, a hardness of 85, and a compression rate of 3%. The fine polishing process specifically includes: A black frosted leather polishing pad is used, and the fine polishing liquid is supplied for polishing; The polishing disc rotation speed is 20 rpm to 30 rpm, the polishing pressure is 200 gf / cm², the fine polishing solution flow rate is 80 mL / min, and the fine polishing time is 1.5 h. The black frosted leather polishing pad has a thickness of 1.45mm, a warp tensile strength of 642N / cm³, a weft tensile strength of 511N / cm³, a warp elongation at break of 53%, a weft elongation at break of 86%, a warp tear strength of 57N, and a weft tear strength of 56N.

5. The polishing method for β-Ga2O3 (100) with a 6° off-center crystal plane according to claim 4, characterized in that, After the rough polishing process is completed, the single wafer is cleaned to remove residual rough polishing solution and impurities from the surface before entering the fine polishing process.

6. The polishing method for β-Ga2O3 (100) off-center 6° crystal plane according to claim 4, characterized in that, After polishing, the single wafer is cleaned and dried.